Comparative analysis of affine transformations expansions in the problem of normalization of images - Зройчикова, Е. В.; Путятин, Е. П. (Bulletin of National Technical University "KhPI". Series: System Analysis, Control and Information Technologies, 2013)
There have been analyzed different decompositions of affine transformations on the subgroup of elementary geometric transformations performed sequentially. The influence of these decompositions to image normalization has been investigated, the comparative analysis has been made. There have been proposed a choice of normalization parameters for each elementary transformation based on the image moment characteristics.